Spatial Variation in Respiratory Disease in Hamilton, Ontario - Nordoff, Andrea (My University, 1991)
The main objective of this study is to examine the effects of the outdoor environment as well as confounding indoor environmental factors upon school-age children in Hamilton, Ontario. This research paper allows for the spatial variation of respiratory disease to be outlined according to five regions of Hamilton: West Mountain, East Mountain, West Lower, East Lower, and North Barton. Due to the high concentration of pollution in the East Lower region, the area north of Barton Street was considered a region in itself. Information was obtained from a study conducted by Dr. L. D. Pengelly of the Urban Air Environment Group and Department of Medicine of McMaster University in 1982. The sample used in the study consisted of 3500 school-age children in conjunction with the Hamilton Board of Education. The data was collected in two ways: a questionnaire conducted by a trained interviewer which took place in the individual household, regarding the child's health history, their home and family as well as pulmonary testing within the schools. Sample characteristics were compiled to evaluate response variations between regions. The results show that as the outdoor environment worsens or approaches the industrial core, several respiratory symptoms increase in occurrence indicating the impact of external pollution on respiratory health. The key indoor factor of parental smoking tends to have the most effect on respiratory symptoms, especially wheeziness for all five regions of Hamilton with gas stove use and forced air heating showing little if any significance.
Title: Spatial Variation in Respiratory Disease in Hamilton, Ontario, Author: Andrea Nordoff, Location: Thode